Allen Squires in Cook's Cove, St. Philip's - Squires, Allen; Squires, Pearl (1962)
Photograph of Allen Squires sitting on rocky beach. Identified by Pearl Squires slide label as “Al's first day in bathing, Cook's Cove, St. Philip's, N.F.”